Exchange Rate Unification in Nigeria: Volatility Dynamics and Short-Term Forecasts - Ayodeji, Idowu (Organizations and Markets in Emerging Economies, 2026)
Nearly two years after Nigeria’s exchange rate unification policy was introduced, questions remain about its effectiveness. This study uses the Exponential GARCH model to examine: (1) the impact of the policy on exchange rate returns and volatility, (2) whether it has achieved its intended goal of long-term stabilization, and (3) what forecasts reveal about future exchange rate dynamics. Results indicate that while the policy did not significantly affect mean returns, it led to a significant increase in volatility (4.3757, p < 0.05). However, volatility began to subside from Q4 2024, suggesting a market adjustment phase. Forecasts show a continued decline in volatility through mid-2025, implying the policy may be on track toward achieving its long-term goals. The study recommends ongoing monitoring of exchange rate behaviour, complementary short-term measures to manage short-term volatility while allowing the unification policy to mature further, and improved policy communication with market participants to support sustained stability.